2013
DOI: 10.1121/1.4798666
|View full text |Cite
|
Sign up to set email alerts
|

Latency of tone-burst-evoked auditory brain stem responses and otoacoustic emissions: Level, frequency, and rise-time effects

Abstract: Simultaneous measurement of auditory brain stem response (ABR) and otoacoustic emission (OAE) delays may provide insights into effects of level, frequency, and stimulus rise-time on cochlear delay. Tone-burst-evoked ABRs and OAEs (TBOAEs) were measured simultaneously in normal-hearing human subjects. Stimuli included a wide range of frequencies (0.5-8 kHz), levels (20-90 dB SPL), and tone-burst rise times. ABR latencies have orderly dependence on these three parameters, similar to previously reported data by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
68
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 38 publications
11
68
2
2
Order By: Relevance
“…Although basilar membrane data are not available for humans and mice, there also seems to be break in SFOAE group delays around 1-2 and 10-15 kHz, respectively (Siegel 2008;Shera et al 2010). In agreement with the human SFOAE data, Rasetshwane et al (2013) reported that latencies of TEOAEs were shorter than forward travel times extracted from auditory brainstem responses at frequencies below 1.5 kHz, while the opposite trend was observed at higher frequencies. It has been proposed that this break in SFOAE group delays marks a transition between basal-and apical-like behaviors (Shera and Guinan 2003;Shera et al 2010).…”
Section: Differences In Low-versus High-frequency Cochlear Responses supporting
confidence: 86%
“…Although basilar membrane data are not available for humans and mice, there also seems to be break in SFOAE group delays around 1-2 and 10-15 kHz, respectively (Siegel 2008;Shera et al 2010). In agreement with the human SFOAE data, Rasetshwane et al (2013) reported that latencies of TEOAEs were shorter than forward travel times extracted from auditory brainstem responses at frequencies below 1.5 kHz, while the opposite trend was observed at higher frequencies. It has been proposed that this break in SFOAE group delays marks a transition between basal-and apical-like behaviors (Shera and Guinan 2003;Shera et al 2010).…”
Section: Differences In Low-versus High-frequency Cochlear Responses supporting
confidence: 86%
“…Leveldependent changes in the latencies of physiological measures including otoacoustic emissions (Shera et al, 2002;Sisto and Moleti, 2007;Shera et al, 2010), the compound action potential (Eggermont, 1979;Rutten, 1986;Henry et al, 2011), and wave V of the auditory brainstem response (ABR; Neely et al, 1988;Don et al, 1998;Dau, 2003;Elberling and Don, 2008;Strelcyk et al, 2009;Elberling et al, 2010;Rønne et al, 2012;Rasetshwane et al, 2013;Verhulst et al, 2013) have also been attributed to effects mediated at the level of the cochlea. The present study examined the effect of stimulus level on ABR wave V latencies in NH and HL ears.…”
Section: Introductionmentioning
confidence: 99%
“…Wave V presumably originates from the lateral-lemniscal pathway (Møller et al, 1995) in the brainstem, but depends on peripheral processes at the levels of the auditory nerve and cochlea. For instance, wave V latency decreases with increasing frequency (e.g., Gorga et al, 1988;Dau, 2003;Rasetshwane et al, 2013), reflecting the shorter travel time required by the traveling wave to excite more basal (higher-frequency) regions of the cochlea. Additionally, when evoked by rising-frequency chirps designed to compensate for traveling-wave dispersion, the amplitude of wave V is larger than it is for both clicks and falling-frequency chirps (Dau et al, 2000;Elberling and Don, 2008; wave I amplitude exhibits similar behavior- Shore and Nuttall, 1985;Chertoff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latencies of the different components are approximately level invariant and separated in time by a factor of 1.6 (Carvalho et al 2003;Goodman et al 2011;Moleti et al 2012). The difference in component latencies and leveldependent contributions to the total TEOAE underlies the decrease in the total TEOAE's latency with increasing stimulus level (Moleti et al 2012;Rasetshwane et al 2013;Lewis and Goodman 2014). Contributions to the stimulus-frequency (SF) OAE from different-latency components analogous to those in the TEOAE may similarly underlie the level-dependency of SFOAE latency and account for non-monotonicity in SFOAE input/ output (I/O) functions (e.g., Schairer et al 2003;Choi et al 2008;Lewis and Goodman 2014).…”
Section: Introductionmentioning
confidence: 99%